Towards a Phenomenology of Repression - a Husserlian Reply to the Freudian Challenge - Smith, Nicholas (Stockholms universitet, 2010)
This is the first book-length philosophical study of Husserl’s transcendental phenomenology and Freud’s theory of the unconscious. The book investigates the possibility for Husserl’s transcendental phenomenology to clarify Freud’s concept of the unconscious with a focus on the theory of repression as its centre. Repression is the unconscious activity of pushing something away from consciousness, while making sure that it remains active as something foreign within us. How this is possible is the main problem addressed in the work. Unlike previous literature (including Ricœur, Merleau-Ponty and Derrida) this book makes full use of the resources of genetic phenomenology and passivity in the attempt to clarify the Freudian unconscious. The central argument developed is that the structure of the lebendige Gegenwart as the core of Husserl’s theory of passivity consists of preliminary forms of bodily kinaesthesia, feelings and drives in a constantly ongoing process where repression occurs as a necessary part of all constitution. The clarification of Freudian repression thus takes place by showing how it presupposes a broad conception of consciousness such as that presented by Husserl’s genetic phenomenology. By arguing that “repression” is central to any philosophical account of subjectivity, this book takes on the most distinct challenge to philosophy posed by Freud.